2010
DOI: 10.5507/bp.2010.049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Allergy on the Immunomodulatory and Clinical Effects of Long-Term Low-Dose Macrolide Treatment of Nasal Polyposis

Abstract: Aims. Cytokine levels in nasal secretions reflect the inflammatory status of the nasal and paranasal sinus mucosa and the development of mucosal disease. The results of previous investigations suggest that macrolide antibiotics can be effective in treatment of chronic rhinosinusitis and nasal polyposis. The aim of this prospective study was to compare the immunomodulatory and clinical effects of long-term low-dose macrolide treatment of nonatopic and atopic patients with nasal polyposis.Methods. Forty (n = 40)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…In agreement with our findings, Peric et al recently reported that a higherdose clarithromycin treatment (500 mg/day over eight weeks) decreased the size of nasal polyps in 45.45 per cent of non-atopic patients and in 50 per cent of atopic patients, demonstrating similar clinical effects in allergic and non-allergic patients. 21 • Low-dose, long-term clarithromycin has been recommended for treatment of chronic rhinosinusitis without nasal polyps • This study suggests short-term, high-dose clarithromycin is a more effective protocol • The anti-inflammatory properties of macrolides and consequent inhibition of Thelper type 2 inflammation are highlighted…”
Section: Discussionmentioning
confidence: 96%
“…In agreement with our findings, Peric et al recently reported that a higherdose clarithromycin treatment (500 mg/day over eight weeks) decreased the size of nasal polyps in 45.45 per cent of non-atopic patients and in 50 per cent of atopic patients, demonstrating similar clinical effects in allergic and non-allergic patients. 21 • Low-dose, long-term clarithromycin has been recommended for treatment of chronic rhinosinusitis without nasal polyps • This study suggests short-term, high-dose clarithromycin is a more effective protocol • The anti-inflammatory properties of macrolides and consequent inhibition of Thelper type 2 inflammation are highlighted…”
Section: Discussionmentioning
confidence: 96%
“…Altered levels of cytokines and adhesion molecules have been found in many pathological states and have been linked to many diseases such as autoimmune diseases, allergies, cardiovascular diseases and cancer [10][11][12][13][14][15] . The cytokine system constitutes an interacting functional network where the contribution from single cytokines is modulated by the levels of other cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations performed by Perić et al (20,21) demonstrated that after eight weeks treatment by 500 mg single oral dose of clarithromycin daily, RANTES and IL-8 levels in nasal secretion samples fell in both allergic and non-allergic patients with nasal polyposis. Eosinophilic cationic protein (ECP) and tumour necrosis factor (TNF)-α levels fell in non-atopic patients, whereas IL-6 and IL-1β concentrations fell in atopic patients with nasal polyps (20,21). So, long-term, low-dose clarithromycin administration has similar anti-inflammatory and variable immunomodulatory effect in these patients.…”
Section: Discussionmentioning
confidence: 92%
“…In vitro roxithromycin administration directly suppresses IL-6 and RANTES production from cultured nasal polyp fibroblasts via the inhibition of IL-6 and RANTES messenger RNA expression (6). Previous investigations performed by Perić et al (20,21) demonstrated that after eight weeks treatment by 500 mg single oral dose of clarithromycin daily, RANTES and IL-8 levels in nasal secretion samples fell in both allergic and non-allergic patients with nasal polyposis. Eosinophilic cationic protein (ECP) and tumour necrosis factor (TNF)-α levels fell in non-atopic patients, whereas IL-6 and IL-1β concentrations fell in atopic patients with nasal polyps (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation